Problematika Rekaman Tanpa Izin sebagai Alat Bukti dalam Perkara Perzinahan antara Kepastian Hukum dan Perlindungan Privasi - Aldo Rajendra Zufar Wahyu Aryaputra; Ni Gusti Agung Ayu Mas Tri Wulandari; I Made Wirya Darma; I Putu Edi Rusmana (AKADEMIK: Jurnal Mahasiswa Humanis, 2026)
This study examines the legal status of recordings obtained without consent as evidence in adultery cases, particularly in relation to the tension between legal certainty and the right to privacy. The main problem lies in the absence of clear legal standards governing the admissibility of such evidence, which creates uncertainty in judicial practice. This research aims to analyze the validity of unauthorized recordings as evidence and to assess their implications for privacy protection within the Indonesian legal framework. The study employs a normative juridical method using statutory and conceptual approaches, focusing on relevant regulations such as the Criminal Procedure Code, the Electronic Information and Transactions Law, and the Personal Data Protection Law, as well as constitutional court decisions. The findings indicate that although such recordings may be considered as supporting evidence under certain conditions, their use raises serious concerns regarding violations of privacy rights. The lack of consistent legal interpretation further complicates their admissibility in court. Therefore, clearer legal guidelines are necessary to balance evidentiary needs with the protection of fundamental rights.